INTEGRATING BILINGUAL STORYTELLING AND DIGITAL VISUALIZATION TO STIMULATE NON-NATIVE ENGLISH-SPEAKING STUDENTS’ LANGUAGE LEARNING - Kurniawan, Mozes; Wijayaningsih, Lanny (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
The increase in digital content that is accessed by all age levels, including ages 4-6 who are in Early Childhood Education, has a good impact on access to positive content for self-development but also has the potential to have negative impacts such as addiction, lack of social interaction, bad influences on physical to weakening language development. Sometimes, the lack of exposure to the use of English contributes to the less-than-optimal mastery of English in children. There is an idea that aims to integrate three components of learning, namely digital technology, storytelling, and the use of bilingualism. Bilingual digital storytelling is an alternative solution to accommodate the development needs of children in terms of receptive language skills, listening and productive language skills, speaking, with the use of two languages as a bridge for children to get used to using English in a tiered manner. Therefore, this study uses the Classroom Action Research type with respondents, namely students aged 4-6 years. Data collection uses observation techniques that refer to observation guide instruments and documentation as additional data to enrich data acquisition. The analysis is carried out descriptively by following several stages of the cycle and comparisons between the entire cycle that runs. The result shows that bilingual digital storytelling demonstrated encouraging progress in English vocabulary acquisition and usage among early learners. However, there was a noticeable gap in developing conversational skills, as most attempts at conversation remained limited to fragmented expressions rather than complete sentences.